2009
DOI: 10.1111/j.1524-4725.2009.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of 10,600-nm Carbon Dioxide Fractional Laser for Acne Scars in Asian Patients

Abstract: We suggest that CO(2) FS used with a combination of two different treatment modes may provide a new treatment algorithm for acne scars in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 21 publications
10
118
0
2
Order By: Relevance
“…In the present study, it was found that three sessions of ablative fractional CO 2 laser showed significant qualitative and quantitative improvement of atrophic acne scars, which was consistent with previous reports of Chapas et al [32] , Manuskiatti et al [33] and Cho et al [34] . However, Mohammad LM, et al…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, it was found that three sessions of ablative fractional CO 2 laser showed significant qualitative and quantitative improvement of atrophic acne scars, which was consistent with previous reports of Chapas et al [32] , Manuskiatti et al [33] and Cho et al [34] . However, Mohammad LM, et al…”
Section: Discussionsupporting
confidence: 82%
“…Various authors had reported a concomiGiant seborrheic keratosis of the face -an unusual presentation 26 doi: 10.18282/jsd.v1.i1. 34 tant occurrence of malignant growth associated with seborrheic keratosis, although without strong association of it [4][5][6][7][8][9] . Unusually large-sized seborrheic keratoses are rarely reported, and their clinical significance is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was found that three sessions of ablative fractional CO 2 laser showed significant qualitative and quantitative improvement of atrophic acne scars, which was consistent with previous reports of Chapas et al [32] , Manuskiatti et al [33] and Cho et al [34] . However, Azzam et al reported that patients with boxcar scars showed no improvement using (15 mJ) power by fractional CO 2 laser with appearance of pixilated pattern and acne activation in some cases [24] .…”
Section: Discussionsupporting
confidence: 82%
“…Fraksiyonel lazerlerin ablatif lazerlere göre daha düşük yan etkilerinin olmasına rağmen, postinflamatuvar hiperpigmentasyon, akne alevlenmesi, herpes enfeksiyonları gibi ciddi yan etkiler bazen görülebilmektedir 8 . Bunun yanında eritem, ödem, skuam ve kurutlanma gibi hafif yan etkiler hem ablatif hem minimal ablatif lazer sistemlerinde görülmektedir 11 . Çalışmamızda eritem hastaların %16,8'inde görüldü ve 3 günden fazla sürdü.…”
Section: Discussionunclassified